Martin & Mahalia : his words, her song - Pinkney, Andrea Davis (Little, Brown and Co., 2013)
Explores the intersecting lives of civil rights leader Martin Luther King, Jr. and gospel singer Mahalia Jackson at the historic moment when their joined voices inspired landmark changes.